Development The Re-Balancing of Economic Powers - Vaggi, Gianni (Springer International Publishing, 2018)
This book provides a brief history of the concept of development and policies relating to it. Readers will find an overview of how development has been discussed and debates from 1950 to the present. The author argues that development is a dialectic relationship between people's empowerment and the existing social and economic structures. Chapters examine well-known economic growth models from Harrod in 1939 to Solow in 1956, but it contends that contemporary issues on development can be better understood with the help of the founding fathers of economics, namely Smith and Marx. The work offers some examples of how to re-balance the existing economic powers with the problem of long-term financing for development in mind.